Resilience as an Emergent European Project? The EU's Place in the Resilience Turn. (22nd May 2019) - Joseph, Jonathan; Juncos, Ana E.
Abstract: This article looks at the development of the resilience approach in EU foreign policy. Building state and societal resilience in the EU's neighbourhood has been identified as one of the key priorities in the EU global strategy. Here we critically analyse these developments and seek to provide an account of the complex dynamics within which the EU's approach to resilience is located. We argue that EU resilience‐thinking is influenced by three broad dynamics – the neoliberal and Anglo‐Saxon approaches to resilience in the sphere of global governance; the particular normative discourse of the EU as a certain type of global actor (the EU as a normative/liberal power); and the multilevel character of the EU with its complex institutional structure and path dependencies which results in decoupling. As a consequence, the 'translation' of resilience constitutes an emergent project at the EU level, but also brings with it new challenges. The argument will be illustrated through a study of the EU global strategy and the Joint Communication on resilience in the neighbourhood.